2015
DOI: 10.1136/annrheumdis-2015-208025
|View full text |Cite
|
Sign up to set email alerts
|

Elevated calprotectin levels reveal bowel inflammation in spondyloarthritis

Abstract: IntroductionMicroscopic bowel inflammation is present in up to 50% of patients with spondyloarthritis (SpA) and is associated with more severe disease. Currently no reliable biomarkers exist to identify patients at risk. Calprotectin is a sensitive marker of neutrophilic inflammation, measurable in serum and stool.ObjectivesTo assess whether serum and faecal calprotectin in addition to C-reactive protein (CRP) can be used to identify patients with SpA at risk of microscopic bowel inflammation.MethodsSerum calp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 19 publications
8
85
2
9
Order By: Relevance
“…92,93 Other studies have described lower or similar CLP serum levels in patients with SpA compared with RA. 88,94 One study by Cypers et al…”
Section: Spondyloarthritismentioning
confidence: 99%
See 2 more Smart Citations
“…92,93 Other studies have described lower or similar CLP serum levels in patients with SpA compared with RA. 88,94 One study by Cypers et al…”
Section: Spondyloarthritismentioning
confidence: 99%
“…97 The mucosal contribution to the increase in circulating CLP levels may explain the modest correlation with SpA disease activity. 94 CLP decreases rapidly upon effective treatment with TNF-a-inhibitors and secukinumab in both axial and peripheral SpA and it has been suggested as a useful biomarker for disease monitoring, where it performs even better than high-sensitivity CRP. 91,95 Baseline CLP was also found to be an independent predictor of radiographic spinal progression in axial SpA in a cohort of German patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of intestinal inflammation in SpA is essentially made using endoscopy as reliable biomarkers are lacking. Recently, however, elevated serum calprotectin and C-reactive protein (CRP) were demonstrated to be independently associated with microscopic bowel inflammation [30]. During intestinal inflammation, fecal calprotectin is elevated because of the migration of neutrophils to the inflamed intestinal mucosa [31].…”
Section: Histologic Changes In the Gut Of Spa Patientsmentioning
confidence: 99%
“…In this study, the authors suggested a screening approach where initially serum calprotectin, CRP, and, if necessary, fecal calprotectin are assessed. The model using this scenario provided an area of 74.4% under the Receiver Operating Characteristic (ROC) curve for the detection of bowel inflammation [30].…”
Section: Histologic Changes In the Gut Of Spa Patientsmentioning
confidence: 99%